A Survey of White Matter Neurons at the Gyral Crowns and Sulcal Depths in the Rhesus Monkey - Mortazavi, Farzad; Romano, Samantha E.; Rosene, Douglas L.; Rockland, Kathleen S. (Frontiers in Neuroanatomy, 2017)
Gyrencephalic brains exhibit deformations of the six neocortical laminae at gyral crowns and sulcal depths, where the deeper layers are, respectively, expanded and compressed. The present study addresses 1) the degree to which the underlying white matter neurons (WMNs) observe the same changes at gyral crowns and sulcal depths, and 2) whether these changes are consistent or variable across different cortical regions. WMNs were visualized by immunohistochemistry using the pan-neuronal label NeuN, and their density was quantified in 8 rhesus monkey brains for four regions; namely, frontal (FR), superior frontal gyrus (SFG), parietal (Par), and temporal (TE). In all four regions, there were about 50% fewer WMNs in the sulcal depth, but there was also distinct variability from region to region. For the gyral crown, we observed an average density per 0.21mm2 of 82 WMNs for the FR, 51 WMNs for SFG, 80 WMNs for Par, and 93 WMNs for TE regions. By contrast, for the sulcal depth, the average number of WMNs per 0.21mm2 was 41 for FR, 31 for cingulate sulcus (underlying the SFG), 54 for Par, and 63 for TE cortical regions. Since at least some WMNs participate in cortical circuitry, these results raise the possibility of their differential influence on cortical circuitry in the overlying gyral and sulcal locations. The results also point to a possible role of WMNs in the differential vulnerability of gyral vs. sulcal regions in disease processes, and reinforce the increasing awareness of the WMNs as part of a complex, heterogeneous, and structured microenvironment.